2006
DOI: 10.1007/s11423-006-9012-7
|View full text |Cite
|
Sign up to set email alerts
|

Teacher, self and peer evaluation of lesson plans written by preservice teachers

Abstract: The study investigated the effects of three types of evaluation on preservice teachers' performance, knowledge and attitudes related to writing lesson plans that incorporate technology. Subjects were randomly assigned to one of the three treatment conditions: teacher-evaluation, self-evaluation or peer-evaluation. All groups completed three class periods of instruction on writing lesson plans, then each subject submitted his/her draft lesson plan. The drafts were evaluated by assigned evaluators (teacher, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 24 publications
0
45
1
1
Order By: Relevance
“…Second, we used elaboration theory (Reigeluth & Stein, 1983), which suggests that multiple attempts at problem-solving be allowed and that the respective problems be sequenced from less to more difficult. Third, while it has been shown that providing students multiple opportunities to demonstrate knowledge and develop ability can result in greater acquisition of learning outcomes (Ozogul, Olina, and Sullivan, 2008;Thompson & Grabau, 2004), practice alone is insufficient. Also needed is relevant feedback from instructors.…”
mentioning
confidence: 99%
“…Second, we used elaboration theory (Reigeluth & Stein, 1983), which suggests that multiple attempts at problem-solving be allowed and that the respective problems be sequenced from less to more difficult. Third, while it has been shown that providing students multiple opportunities to demonstrate knowledge and develop ability can result in greater acquisition of learning outcomes (Ozogul, Olina, and Sullivan, 2008;Thompson & Grabau, 2004), practice alone is insufficient. Also needed is relevant feedback from instructors.…”
mentioning
confidence: 99%
“…Some teacher education programs require preservice teachers to take a stand-alone instructional technology course (Chai, Koh, & Tsai, 2010;Ozogul, Olina, & Sullivan, 2008) as means to developing TPACK. Graham, Cox, and Velasquez (2009) (Niess, 2005), with some requiring preservice teachers to complete subject-specific methods course while dually enrolled in an instructional technology course (Graham, Cox, & Velasquez, 2009 the TPACK framework, provided opportunities for observation of TPACK teaching, and required teachers to apply designed lessons in actual classrooms.…”
Section: Tpack Development For Preservice Teachersmentioning
confidence: 99%
“…Through these design experiences, participants gain a deeper understanding of the interwoven complexities of subject matter, instructional strategies, and technology. As Koehler and Mishra (2005) Most often, the learning by design approach is utilized to structure experiences in which preservice teachers design and implement lesson plans or instructional units (Guzey & Roehrig, 2009;Ozgun-Koca, Meagher, & Edwards, 2009;Jang & Chen, 2010;Ozogul, Olina, & Sullivan, 2008;Niess, 2005). Sometimes, the design experiences are targeted towards specific technologies.…”
Section: Learning By Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozogul, Olina, and Sullivan (2008) explored the use of multiple sources of evaluators for student projects. The participants were pre-service teachers (as in the current study) and the researchers found that feedback from any of three evaluator types, teacher, self, or peer, significantly improved the final form of the assignment.…”
Section: Literature Reviewmentioning
confidence: 99%